SEROLOGICAL SURVEY OF Ehrlichia SPECIES IN DOGS, HORSES AND HUMANS: ZOONOTIC SCENERY IN A RURAL SETTLEMENT FROM SOUTHERN BRAZIL - Vieira, Rafael Felipe da Costa; Vieira, Thállitha Samih Wischral Jayme; Nascimento, Denise do Amaral Gomes; Martins, Thiago F.; Krawczak, Felipe S.; Labruna, Marcelo B.; Chandrashekar, Ramaswamy; Marcondes, Mary; Biondo, Alexander Welker; Vidotto, Odilon (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
The aims of this study were to determine the seroprevalence of Ehrlichia spp. and risk factors for exposure in a restricted population of dogs, horses, and humans highly exposed to tick bites in a Brazilian rural settlement using a commercial ELISA rapid test and two indirect immunofluorescent assays (IFA) with E. canis and E. chaffeensis crude antigens. Serum samples from 132 dogs, 16 horses and 100 humans were used. Fifty-six out of 132 (42.4%) dogs were seropositive for E. canis. Dogs > one year were more likely to be seropositive for E. canis than dogs ≤ one year (p = 0.0051). Ten/16 (62.5%) and 8/16 (50%) horses were seropositive by the commercial ELISA and IFA, respectively. Five out of 100 (5%) humans were seropositive for E. canis and E. chaffeensis. Rhipicephalus sanguineus (n = 291, 97.98%) on dogs and Amblyomma cajennense (n = 25, 96.15%) on horses were the most common ticks found. In conclusion, anti-Ehrlichia spp. antibodies were found in horses; however, the lack of a molecular characterization precludes any conclusion regarding the agent involved. Additionally, the higher seroprevalence of E. canis in dogs and the evidence of anti-Ehrlichia spp. antibodies in humans suggest that human cases of ehrlichiosis in Brazil might be caused by E. canis, or other closely related species.